Isolated ureteral injury from multiple stab wounds: A case report - Seif Mokadem; Ahmed Saadi; Sami Chebbi; Amine Hermi; Sarra Moussa; Marouene Chakroun; Mohamed Riadh Ben Slama (Trauma Case Reports, 2023)
This is a case report about a 44-year-old woman who sustained multiple stab wounds, resulting in an isolated right ureteral injury. Despite a precise diagnosis from an urgent CT scan showing contrast material extravasation, the patient's stable vital signs allowed for a thorough surgical exploration, leading to an accurate diagnosis. Immediate surgical repair of the right ureter using an end-to-end anastomosis following precise surgical principles achieved complete restoration of the initial injuries. The case highlights the accuracy of CT scan assessment, the unreliability of hematuria in diagnosing ureteral injuries, and the need for a high index of suspicion during surgical exploration to avoid overlooking such cases.